Weight trends of children and adolescents during the COVID-19 pandemic and its relationship with psychological distress - Pinheiro, Filipe (2022)
Introduction: The COVID-19 pandemic has led to a biopsychosocial health deterioration in children and adolescents. However, there is a lack of knowledge about its impact on weight status. We aimed to assess the BMI trends in children and adolescents over more than one year of the COVID-19 pandemic. Moreover, we examined the association of their overall BMI change with psychological distress and specific household characteristics. Methods: A cross-sectional study with a retrospective component was carried out in a Portuguese hospital with a convenience sample of 422 children and adolescents (mean age = 12.4 ± 2.9 years) and one of their parents. A validated online questionnaire was administered to both groups to evaluate their psychological distress. Multiple linear regression was used to identify the BMI change predictors. Results: The COVID-19 pandemic resulted in weight gain, but only in children (p<.001) and those with normal weight (p<.001). The first lockdown alone accounted for the observed result, as the remaining time correlated with a gradual decrease in BMI, though insufficient to reach pre-pandemic levels (p=.015). Associated factors included children and adolescents' BMI, stress, and specific household characteristics. Discussion: This study contradicts the hypothesis that weight would increase proportionately to the number of months of school closure. It also underscores children's difficulties in losing the weight gained during the first lockdown. Finally, the association of weight gain with environmental and psychological factors highlights the importance of their consideration in the therapeutical approach to weight gain.